Pembinaan Masyarakat Qur'ani di Kecamatan Manggala Melalui KKN STIBA Makassar - Rachmat bin Badani Tempo; Ahmad Syaripudin; Irsyad Rafi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
Manggala sub-district is one of 14 sub-districts in Makassar city. The area of ​​Manggala sub-district is 24.14 km2 or 13.73% of the area of ​​Makassar City. Manggala sub-district consists of 8 villages namely Bontoala, Bangkala, Batua, Borong, Manggala, Tamangapa, Biring Romang and Antang. The purpose of this STIBA Makassar Real Work Lecture (KKN) batch IV is a form of community service which is a pillar of the Tri Dharma of Higher Education. The method of implementing community service programs begins with mapping the problems and needs of the community using SOAR. After the analysis is carried out, a work program is prepared that is appropriate and needed by the community. Work programs that have been successfully implemented include: socialization and friendship (SS), TKA / TPA management training, TKA / TPA teaching, teaching of the Qur'anic tahfidz, National Seminar on Virtual Arabic (SNBAV), Subuh Reaching Blessings (SMK), Tahfidz Weekends (TW), Learning Yajwid and Halaqah Tahsin, and all of these programs have been running well and have shown initial results in accordance with the stated objectives of the Community Service Program.